Naqada IId: The Birth of an Empire Kingship, Writing, Organized Religion - Josephson, Jack A..
This study explores the genesis of the Egyptian Empire in the Naqada IId period and why the authors believe it originated at that time. It evolved in an era that witnessed unprecedented strides in human achievement. This was in many ways similar to other rare episodes in human history in which radical leaps of innovation unexpectedly and inexplicably appear; it represents a transition from mythological to historical awareness. This period, in which hieroglyphic writing emerges, should no longer be referred to as prehistoric but rather early historic. The comparatively brief time span of this revolution is nothing short of miraculous and requires an acceptance of logical inference supported by the evidence we have gathered from currently available sources.